Recognizing and Treating Anal Cancer: Training Medical Students and Physicians in Puerto Rico - Ortiz, Ana P.; Guiot, Humberto M.; Díaz-Miranda, Olga L.; Román, Leticia; Palefsky, Joel; Colón-López, Vivian (Puerto Rico Health Sciences Journal, 2013)
Objective: This training activity aimed at increasing the knowledge of anal cancer screening, diagnostic and treatment options in medical students and physicians, to determine the interest of these individuals in receiving training in the diagnosis and treatment of anal cancer, and to explore any previous training and/or experience with both anal cancer and clinical trials that these individuals might have. Methods: An educational activity (1.5 contact hours) was attended by a group of medical students, residents and several faculty members, all from the Medical Sciences Campus of the University of Puerto Rico (n = 50). A demographic survey and a 6-item pre- and post-test on anal cancer were given to assess knowledge change. Results: Thirty-four participants (68%) answered the survey. Mean age was 29.6 ± 6.6 years; 78.8% had not received training in anal cancer screening, 93.9% reported being interested in receiving anal cancer training, and 75.8% expressed an interest in leading or conducting a clinical trial. A significant increase in the test scores was observed after the educational activity (pre-test: 3.4 ± 1.2; post-test: 4.7 ± 0.71). Three of the items showed an increase in knowledge by the time the post-test was taken. The first of these items assessed the participants’ knowledge regarding the existence of any guidelines for the screening/treatment of patients with human papillomavirus (HPV)-related anal disease. The second of these items attempted to determine whether the participants recognized that anal intraepithelial neoplasia (AIN) 2 is considered to be a high-grade neoplasia. The last of the 3 items was aimed at ascertaining whether or not the participants were aware that warty growths in the anus are not necessarily a manifestation of high-grade AIN. Conclusion: This educational activity increased the participants’ knowledge of anal cancer and revealed, as well, that most of the participants were interested in future training and in collaborating in a clinical trial. Training physicians from Puerto Rico on anal cancer clinical trials is essential to encourage recruitment of Hispanic patients in these studies now that the guidelines in anal cancer screening and treatment are on their way to be defined.